On the number of representations of positive integers by quadratic forms as the basis of the space S4(Γ0(47),1) - Ahmet Tekcan; Osman Bızım (International Journal of Mathematics and Mathematical Sciences)
The number of representations of positive integers by quadratic forms F1=x12+x1x2+12x22 and G1=3x12+x1x2+4x22 of discriminant −47 are given. Moreover, a basis for the space S4(Γ0(47),1)